THE ANALYSIS OF ENGLISH LEARNING EVALUATION ON A NEW NORMAL ORDER - I Wayan Agus Ariana; Luh Made Dwi Wedayanthi (Language and Education Journal Undiksha, 2022)
This study aims to obtain comprehensive information regarding the evaluation of learning English in the new life order or the new normal era in class X, SMA Hindu (UWP) Astika Dharma at Pempatan Village, Rendang District, Karangasem Regency in Bali related to evaluation planning, evaluation implementation, and evaluation of learning in new life order. The subjects used in this study were teachers and students from school institutions along with evaluation data for English learning. Data were collected by observation, interviews, tests, and documentation, then analyzed descriptively qualitatively using a case study approach. In this study, the results showed that the evaluation plan for learning English in the new life order in the RPP was in accordance with the SK and also adapted to the KD in the syllabus.  Hierarchically the teacher makes learning objectives based on competency standards and emergency curriculum adjustments, determines the time in planning evaluations, and adapts to the characteristics of students based on evaluation principles. The evaluation of English learning in the new life order has been carried out in accordance with the National Competency Standards. The conclusion is that the evaluation of learning English in the new life order in class X SMA Hindu (UWP) Astika Dharma at Pempatan village has been carried out by the teacher in accordance with the Minister of Education and Culture Regulation No 23 of 2020 Regarding Education Evaluation Standard